Micro/Nanostructures and Mechanical Properties of Trabecular Bone in Ovariectomized Rats - Hu, Shidi (Int J Endocrinol, 2015)
Bone mechanical properties encompass both geometric and material factors, while the effects of estrogen deficiency on the material and structural characteristics of bone at micro- to nanoscales are still obscure. We performed a series of combined methodological experiments, including nanoindentation assessment of intrinsic material properties, atomic force microscopy (AFM) characterization of trabecular (Tb) nanostructure, and Tb microarchitecture and 2D BMD. At 15 weeks after surgery, we found significantly less Tb bone mineral density (BMD) at organ (−27%) and at tissue level (−12%), Tb bone volume fraction (−29%), Tb thickness (−14%), and Tb number (−17%) in ovariectomy (OVX) rats than in sham operated (SHAM) rats, while the structure model index (+91%) and Tb separation (+19%) became significantly greater. AFM images showed lower roughness Tb surfaces with loosely packed large nodular structures and less compacted interfibrillar space in OVX than in SHAM. However, no statistically significant changes were in the Tb intrinsic material properties—nanoindentation hardness, elastic modulus, and plastic deformation—nanoindentation depths, and residual areas. Therefore, estrogen deprivation results in a dramatic deterioration in Tb micro/nanoarchitectures, 3D volumetric BMD at both organ and tissue levels, and 2D BMD, but not in the nanomechanical properties of the trabeculae per se.